Penguatan local value chain: analisis pembiayaan hijau terhadap comparative trade CPO di Malaysia - Anwaruddin, Fadli; Sutjipto, Hady (Journal of Economic, Business & Accounting Research, 2023)
This study examines the comparative dysfunction of palm oil in local CPO commodities in Malaysia through green economic structures and strengthening local value chains. The green economy structure variables discussed in this study, namely green financing and local value chain variables in CPO exports, are measured by CPO products' price and CPO production's value. In addition to these variables, household consumption expenditure is the control variable used as a variable affecting the level of CPO exports. The research data uses data from the first quarter of 2013 to the fourth quarter of 2022. This research methodology describes the Autoregressive Distributed Lag (ARDL) model to examine the long-term effect between variables and the Error Correction Model (ECM) to see how quickly the economy returns to a balanced condition when there are short-term shocks. The study results show that the long-term correlation between the variables of green financing, the price of CPO products, and the value of CPO production significantly affects the level of CPO exports. However, the household consumption expenditure variable is insignificant to the level of CPO exports in the long run. Thus, the short-term correlation shows that green financing variables, CPO product prices, CPO production values, and household consumption expenditures significantly affect CPO export levels.